Leadership and Employees’ Innovative Work Behavior: Test of a Mediation and Moderation Model (2012)
The aim of this study is to determine the relationship between Transformational (TFL)/ Transactional (TSL) leadership and employees’ Innovative Work Behavior (IWB), through a mediation and moderation model. The proposed model postulates that Organizational Climate for Innovation (OCI) and Organizational Absorptive Capacity (OAC) exert a mediating role whereas Employees´ Work Engagement (EWE) has a moderating effect in such relationship. A total of 267 Colombian workers from different kind of companies completed a reliable battery of questionnaires. The sample was collected through the MBA programs from two recognized universities located in Bogotá, Colombia. Structural equation modeling and hierarchical regression analyses were used to test the proposed model. According to the results, there is a direct and positive relationship between TFL and IWB as was expected. However, contrary to what had been hypothesized, TSL demonstrated to exert the same positive linkage. OCI and OAC showed its mediator effect in the relationship between TFL/TSL and IWB, nevertheless, this effect was less strong than when the relationship between theses variables was direct. On the contrary, EWE does not exert a moderator effect in this relationship as it was posited, but shows a significant and direct relationship with IWB. This research allows assert that leadership influences IWB, either directly or mediated by organizational variables. These results contribute to extent the literature in a scarcely studied field, by testing an empirical model.